Restorying the present by revisiting the past: Unexpected moments of discovery and illumination through museum learning. Issue 2 (November 2016) - Kawalilak, Colleen; Groen, Janet
Two adult educators, guided by autoethnography as methodology, share the re storying of their own lifelong learning narratives and unexpected insights gained from having experienced the powerful potential of museum learning and culture. Having previously regarded museum visits as an experience that primarily tapped the intellectual, cognitive domain, the authors, drawing from experiencing the Pier 21 Museum in Halifax and the War Brides installation exhibit at the Glenbow Museum, Calgary, were thrust into multiple ways and dimensions of how we learn, how we view the world, and how we locate ourselves in the world. Shared stories illuminate the potential for museum education to animate, breathe life into and offer a deepened understanding of our own personal, lifelong learning narratives.